White Teacher, Know Thyself: Improving Anti-Racist Praxis Through Racial Identity Development - Utt, Jamie; Tochluk, Shelly (Urban education (Beverly Hills, Calif.), 2020)
This article asserts that White teachers in urban schools must turn their racialized focus away from implied deficits of students of Color in the “achievement gap” frame and toward the impact their racial identities have on their craft. Through empirical analysis of White teachers’ experiences, the article suggests six areas of self-work for developing positive, anti-racist White racial identities, an integral component in culturally responsive teaching. The authors draw upon Zeus Leonardo’s “third space” of navigating Whiteness and Janet Helms’s racial identity development framework to offer practical suggestions for building more anti-racist and effective pedagogy.